2022
DOI: 10.3390/jcm12010033
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Anterior Cingulate Cortex and Its Relation to Schizophrenia

Abstract: Cortical folding of the anterior cingulate cortex (ACC), particularly the cingulate (CS) and the paracingulate (PCS) sulci, represents a neurodevelopmental marker. Deviations in in utero development in schizophrenia can be traced using CS and PCS morphometry. In the present study, we measured the length of CS, PCS, and their segments on T1 MRI scans in 93 patients with first- episode schizophrenia and 42 healthy controls. Besides the length, the frequency and the left-right asymmetry of CS/PCS were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…A growing number of empirical findings identify relationships between the morphology of indentations (known as sulci) in the cerebral cortex and individual differences in cognition (e.g., as reviewed in Cachia et al, 2021;Mangin et al, 2019;Weiner, 2019Weiner, , 2023. For example, sulcal morphology in various human association cortices that have expanded significantly throughout evolution has been related to individual differences in abstract reasoning, executive function, inhibitory control, memory, face processing, and reading, as well as psychopathology (Amiez et al, 2018;Borst et al, 2014;Cachia et al, 2014;Garrison et al, 2015;Im et al, 2016;Lahutsina et al, 2023;Maboudian et al, 2024;Parker et al, 2023;Tissier et al, 2018;Voorhies et al, 2021;Willbrand et al, 2022;Yao et al, 2022). Moreover, recent research suggests that individual differences in sulcal interruptions are also related to individual differences in cognitive abilities such as numerical processing (Roell et al, 2021;Schwizer Ashkenazi et al, 2024), language and memory (Santacroce et al, 2024), and reading (Borst et al, 2016;Cachia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of empirical findings identify relationships between the morphology of indentations (known as sulci) in the cerebral cortex and individual differences in cognition (e.g., as reviewed in Cachia et al, 2021;Mangin et al, 2019;Weiner, 2019Weiner, , 2023. For example, sulcal morphology in various human association cortices that have expanded significantly throughout evolution has been related to individual differences in abstract reasoning, executive function, inhibitory control, memory, face processing, and reading, as well as psychopathology (Amiez et al, 2018;Borst et al, 2014;Cachia et al, 2014;Garrison et al, 2015;Im et al, 2016;Lahutsina et al, 2023;Maboudian et al, 2024;Parker et al, 2023;Tissier et al, 2018;Voorhies et al, 2021;Willbrand et al, 2022;Yao et al, 2022). Moreover, recent research suggests that individual differences in sulcal interruptions are also related to individual differences in cognitive abilities such as numerical processing (Roell et al, 2021;Schwizer Ashkenazi et al, 2024), language and memory (Santacroce et al, 2024), and reading (Borst et al, 2016;Cachia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The frontal cortex, temporal pole, dorsal anterior cingulate cortex (ACC), and putamen are involved in pathogenesis of SZ [27]. Lahutsina et al suggested that the ACC gray matter reductions may presage psychosis onset [28]. Another study focused on the role of redox imbalance/mitochondrial dysfunction and implicate interneuron subtypes in ACC in SZ pathophysiology [29].…”
Section: Introductionmentioning
confidence: 99%